Correlation between ejaculate characteristics and sperm abnormalities in boars exposed to summer heat stress - Petrović Aleksandra; Bogdanović Vladan; Radović Čedomir; Gogić Marija; Živković Vladimir; Stojiljković Nenad; Savić Radomir (Biotechnology in Animal Husbandry)
Seasonal heat stress is a well-known factor that negatively affects boar fertility, primarily by reducing semen quality and increasing the incidence of abnormal spermatozoa. This study aimed to investigate the relationship between ejaculate characteristics and sperm morphological abnormalities in boars during the most sensitive period of the year. Between August and October, a total of 129 ejaculates were collected from 17 boars. The analyzed semen traits included ejaculate volume, sperm concentration, total and functional sperm counts, motility (in native and diluted semen), viability, and the presence of morphological abnormalities, specifically head, tail, acrosomal defects, and protoplasmic droplets. The results showed that only sperm motility and the number of produced doses significantly correlated with abnormal sperm forms. A weak but consistent positive correlation (r f>0.200; p<0.05 or p<0.01) was observed between certain categories of abnormalities, particularly between secondary forms (such as protoplasmic droplets) and primary defects in the tail and acrosomal region. Correlations among primary abnormalities were generally weak. These findings highlight the importance of monitoring sperm motility and morphology as early indicators of heat stress effects in boars.